Using the developmental rubric as a tool in the teaching of academic writing - Mohd. Asraf, Ratnawati; Md Zamin, Ainul Azmin (ASIAN ESL JOurnal Press, 2017)
This paper describes the results of a study that investigated the use and pedagogical potential of the developmental rubric in the teaching of writing to tertiary-level students of English for Academic Writing (EAW). Five teachers were interviewed on the use of the rubric for self-editing and peer feedback. The findings showed that the teachers felt that the rubric was a useful tool for providing feedback as well as for teaching, and that it could create a learning environment that was conducive to achieving the learning outcomes. The study concluded that the developmental rubric has an enormous potential to be used as a tool for the teaching of academic writing, but that efforts should be made to ensure that the items in the rubric correspond with the content to be graded.